IMPLEMENTATION OF E-LEARNING AS A MEDIA FOR BIOLOGY LEARNING BY HIGH SCHOOL TEACHERS IN BIREUEN DISTRICT - Nurlia Zahara; Rizky Ahadi (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2022)
The advantages of developing and implementing information technology in education include increased learning effectiveness and flexibility, as well as making the learning process easier for teachers and students. The study was conducted in the even semester of the 2018/2019 academic year in Bireuen Regency to determine the use of e-learning as a medium for high school biology learning. Mix methods research was used in this study. The participants in this study were all Bireuen Regency public high school teachers. The participants in this study were 12 biology teachers from SMAN 1 Bireuen, SMAN 2 Bireuen, and SMAN 2 Peusangan. A questionnaire is used to collect information. The data were analyzed using the percentage formula. The results showed that the use of e-learning as a medium for biology learning by teachers at SMA Bireuen Regency in terms of several criteria, namely e-learning planning was 77.08% and e-learning implementation was 72.50%. So it can be concluded that the use of e-learning as a medium for learning biology by teachers in senior high schools in Bireuen Regency as a whole is effective.